2017
DOI: 10.1055/s-0043-109696
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Level Induces Cardiovascular Dysplasia During Early Embryo Development

Abstract: The incidence of gestational diabetes mellitus (GDM) has increased dramatically amongst multiethnic population. However, how gestational diabetes mellitus damages the developing embryo is still unknown. In this study, we used yolk sac membrane (YSM) model to investigate angiogenesis in the developing chick embryo. We determined that in the presence of high glucose, it retarded the growth and extension of the embryonic vascular plexus and it also reduced the density of the vasculature in yolk sac membrane model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…It has been reported that the majority of placentas from GDM pregnancies exhibit increased [22] or abnormal angiogenesis [23,24]. Our present data revealed that the placental weights from the GDM pregnancies were significantly increased compared with those of the normal healthy controls (Table 1).…”
Section: Figsupporting
confidence: 63%
“…It has been reported that the majority of placentas from GDM pregnancies exhibit increased [22] or abnormal angiogenesis [23,24]. Our present data revealed that the placental weights from the GDM pregnancies were significantly increased compared with those of the normal healthy controls (Table 1).…”
Section: Figsupporting
confidence: 63%
“…Gestational diabetes mellitus is a relatively common condition in pregnancy, especially in the second and the third trimester, and influences up to 5% of pregnant population . Maternal hyperglycemia may affect fetal development, especially cardiovascular system, and might lead to myocardial hypertrophy . Evaluation of fetal cardiac function in utero has always been a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al reported that the myocardium in the right ventricle and left atrium were significantly thicker than the control and also there was a reduction in glycogen content in cardiomyocytes. The high glucose also induced excess reactive oxygen species (ROS) production in the cardiomyocytes . These results suggest that GDM greatly influences the development of fetal heart.…”
mentioning
confidence: 94%
“…However, the increased maternal blood glucose is considered the primary teratogenic agent in diabetic pregnancies. Previous studies in animal models have shown that even in the absence of DM, hyperglycemia alone can increase the risk of embryopathies [63,64]. Even a transient increase in glucose levels during early gestation (equivalent to the first eight weeks of gestation in humans), also known as the critical period of embryonic development, resulted in higher rates of congenital malformations in the offspring [65].…”
Section: Hyperglycemia Teratogenicity During Heart Developmentmentioning
confidence: 99%